ALTERNATIF PENGENDALIAN LIMPASAN PERMUKAAN DI PERKOTAAN DENGAN MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Mananoma, Tiny; Moningka, Frederiko Marchiano Imanuel (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
Control of surface runoff is a major challenge in sustainable urban stormwater management. High rainfall can cause various problems such as floods and landslides. Related to the problem of surface runoff includes a number of problems that require attention and good solutions to maintain environmental sustainability and prevent negative impacts from surface runoff. Surface runoff control activities generally tend to be social, technically costly, and relatively long. Collaboration with experts, government, and local stakeholders can also reinforce the concept of successful surface runoff control. The application of the AHP (Analytical Hierarchy Process) method is needed as a systematic approach to evaluate and select effective alternative surface runoff control systems, in this study four alternatives were taken based on three criteria. These alternatives involve solutions such as the application of biopores of infiltration wells, rainwater harvesting, retention ponds and green open spaces then these alternatives are evaluated based on relevant criteria, in this study the relevant criteria are taken namely technically, environmentally and cost. The results of this analysis using the AHP method provide relative priority values for each alternative, allowing for the selection of optimal solutions to surface runoff problems. Based on this assessment, it shows that alternative green open space is an optimal solution for surface runoff control systems in urban areas.